Heterologous Expression and Functional Characterization of Catalytic Subunit of Rice Acetohydroxyacid Synthase - Arabzadeh, Ghazaleh; Shahpiri, Azar (Protein and Peptide Letters, 2019)
Background: Acetohydroxyacid Synthase (AHAS) is the first enzyme in the biosynthesis pathway of the branched chain amino acids. AHAS is the common target site of five herbicide chemical groups: sulfonylurea, imidazolinone, triazolopyrimidine, pyrimidinyl-thiobenzoates, and sulfonyl-aminocarbonyl-triazolinone. Objective: The purification of protein enabled us to study the physical and biochemical properties of the enzyme. In addition in vitro activity of this enzyme was tested in the presence of four different sulfonylureaherbicides and the feedback regulation of enzyme was analyzed in the presence of branched amino acids. Methods: The gene encoding catalytic subunit of rice AHAS (cOsAHAS) without part of the chloroplast transit sequence was cloned into the bacterial expression vector pET41a and heterologously expressed in Escherichia coli as carboxy-terminal extensions of glutathione-S-transferase (GST).The soluble protein was purified using affinity chromatography. The measurement of GSTOsAHAS activity was performed under optimized conditions at present of branched-chain amino acids and sulfonylurea herbicides independently. Results: The optimum pH and temperature for GST-cOsAHAS activity was 8.0 and 37 °C, respectively. The specific activity and Km value of this enzyme toward pyruvate were 0.08 U/mg and 30 mM, respectively.GST-cOsAHAS was inhibited by herbicides tribenuron, sulfosulfuron, nicosulfuron and bensulfuron while the enzyme was insensitivieto end products. Conclusion: These results suggest that the recombinant form of GST-cOsAHAS is functionally active and carries the binding site for sulfynylurea herbicides. Furthermore, GST-cOsAHAS was insensitive to feedback inhibition by endproducts which indicates the existence of a regulator subunit in rice AHAS as previously has been described in other plant AHASs.
Keywords: rice